(untitled) (Asian Journal of Medical and Biological Research, 2020)
This study was aimed exploring the cytotoxicity and antimicrobial activity of the leaves D. thwaites is an endemic plant to Sri Lanka. The plant is known for its nutritional and medicinal applications where especially the leaf decoctions are being used to wash skin wounds in indigenous medicine. The brine shrimp lethality assays was performed to evaluate normal toxicity and it gave LC50 value greater than 1000 μg/ mL showing that the plant extracts are non-toxic to the normal cells. The agar-well diffusion assay was performed to assess the antimicrobial activity, and strains of bacteria; E. coli, Staphylococcus aureus, Pseudomonas aeruginosa and Methicillin Resistant Staphylococcus aureus (MRSA) and fungus; Candida albicans were used as test organisms. The results indicated that all the extracts are active against Staphylococcus aureus (Gram Positive) with maximum inhibition shown for methanolic and aqueous extracts. When it was tested against MRSA both aqueous and methanolic extracts gave similar inhibitions. The minimal inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined as 6.25 mg/mL and 100 mg/mL respectively with S. aureus whereas no inhibition observed by any of the extract against Gram negative bacteria and Candida albicans. Thus, this study revealed the leaves of D. thwaites possesses strong anti-bacterial activity against S. aureus and MRSA. The results confirmed the efficacy of using D. thwaites as the natural antimicrobial agent and suggested to develop the leaves into value added products to be used in topical applications as antiseptic solutions or ointments. Asian J. Med. Biol. Res. June 2020, 6(2): 316-320